The Plant-Level View of Korea's Growth Miracle and Slowdown - Munseob Lee; Yongseok Shin (Institute of Labor Economics (IZA), 2023)
We analyze the evolution of the plant size distribution, static allocative efficiency, and business dynamism of the Korean manufacturing sector during its growth miracle (1967–2000) and the subsequent slowdown since 2000. The average plant size has an inverse-U pattern over time, uncorrelated with the level or the growth rate of value-added per worker. The measure of static misallocation decreases modestly until 1983, consistent with the fast economic growth, but increases substantially afterwards, without a corresponding negative trend in manufacturing productivity. These results are seemingly at odds with existing cross-country evidence on the relationship between plant size and economic development, as well as the one between static allocative efficiency and development. In addition, business dynamism, measured by either churning or responsiveness to shocks, diminished significantly since 2000, coinciding with the slowdown in manufacturing productivity. Our findings call for more systematic research on how economic growth correlates with establishment/firm size distribution and with static and dynamic allocative efficiency.
Keywords: O14; O47; O53; 330; size distribution; misallocaton; business dynamism